Կանանց պատկերատիպերի վաղագույն դրսևորումները Հայկական լեռնաշխարհում - Վիկտորյա Վասիլյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается проблема возникновения типологии женских изображений в Армянском нагорье. Первыми проявлениями женского образа в Армянском нагорье являются петроглифы. This article is concerned with the issue of the origin of the typology of female images in Armenian Highlands. The first female images are in petroglyphs.
Keywords: Archaeology; Fine Arts; Sculpture; Mural Painting